Diana Rodríguez Pérez (ed.). Greek Art in Context: Archaeological and Art Historical Perspectives. - Osborne, Robin (Journal of Greek Archaeology, 2018)
As the editor observes, ‘context’ has become a buzzword. Why? The editor has concluded, following the 2014 Edinburgh conference designed ‘to discuss the issue [of context] and clarify its terms’, from which this book derives, that ‘How each of us understands the term depends on one’s field of specialization and on the nature of the material under study’. That seems to me nonsense. What context is relevant depends on the question being answered. It is not whether something is a pot or a statue, or whether I am an historian or an archaeologist or an art historian that matters, it is what I want to know.